2020
DOI: 10.1371/journal.pntd.0008618
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and deep sequencing analysis of extracellular vesicles isolated from adult male and female Schistosoma japonicum

Abstract: Schistosomes are the causative agent of schistosomiasis, which affects more than 200 million people worldwide. Unlike other trematode parasites, schistosomes (along with the Didymozoidae) have evolved separate sexes. Pairing of males and females is a prerequisite for female sexual development and subsequent egg production. However, the mechanisms underlying these processes remain poorly understood. Extracellular vesicles (EVs) have been shown to play important roles in many biological processes. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Significant egg count and granuloma size reduction in group III could be linked to the reduction of the adult worm load in addition to the decoupling effect. Du et al (2020) showed that cargo of S. japonicum EVs plays an important role in egg production [42]. Inhibition of this role may be an additional factor that led to reduction in the egg count.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Significant egg count and granuloma size reduction in group III could be linked to the reduction of the adult worm load in addition to the decoupling effect. Du et al (2020) showed that cargo of S. japonicum EVs plays an important role in egg production [42]. Inhibition of this role may be an additional factor that led to reduction in the egg count.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…An interesting observation that arises from the accumulated data is that the three main classes of parasites secrete 20S proteasome subunits (Figure 1). With respect to the helminths, 20S proteasome subunits were found encapsulated in the EVs of Trichuris muris (Eichenberger et al, 2018), Fasciola hepatica (Cwiklinski et al, 2015), Schistosoma japonicum (Du et al, 2020;Zhu et al, 2016), Schistosoma haematobium (Mekonnen et al, 2020) and Echinococcus granulosus (Nicolao et al, 2019). 20S proteasome subunits were also identified in EVs secreted by the protozoa Giardia lamblia (Stefanic et al, 2006), Trichomonas vaginalis (Nievas et al, 2018), Leishmania donovani (Silverman et al, 2010), Leishmania major (Atayde et al, 2015), Leishmania infantum (Douanne et al, 2020), Toxoplasma gondii (Wowk et al, 2017) and Acanthamoeba castellanii (Lin et al, 2019).…”
mentioning
confidence: 99%
“…Exosome roles in parasite diseases have been increasingly noted in recent years, including in the infection of protozoa ( Leishmania and Trichomonas ), fungi ( Cryptococcus neoformans and Paracoccidioides brasilensis ), and helminths such as Heligmosomoides polygyrus , S. mansoni , and S. japonicum ( 18 , 30 34 ).…”
Section: The Roles Of Exosomes In Host–parasite Interactionsmentioning
confidence: 99%
“…Through advanced isolation, proteomic characterization, and high-throughput sequencing techniques, researchers have successfully identified a large population of exosomal proteins and miRNAs released by S. japonicum , S. mansoni , and S. haematobium ( 33 , 34 , 37 40 ). However, the cargo profiles can vary in exosomes from the different stages, for instance, their eggs, schistosomula (<15 days), and adult worms (22–35 days) ( 33 , 34 , 37 40 ). Thus, understanding the components in different stages may contribute to better schistosomiasis control strategies.…”
Section: Exosomal Cargoes In Schistosomiasis Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation